The Impact of Host Genotype, Intestinal Sites and Probiotics Supplementation on the Gut Microbiota Composition and Diversity in Sheep - Xiaoqi Wang; Zhichao Zhang; Xiaoping Wang; Qi Bao; Rujing Wang; Ziyuan Duan (Biology, 2021)
Three sampling strategies with a 16s rRNA high-throughput sequencing and gene expression assay (by RT-PCR) were designed, to better understand the host and probiotics effect on gut microbiota in sheep. Sampling: (1) colon contents and back-fat tissues from small-tailed Han sheep (SHS), big-tailed Hulun Buir sheep (BHBS), and short-tailed Steppe sheep (SHBS) (n = 12, 14, 12); (2) jejunum, cecum and colon contents, and feces from Tan sheep (TS, n = 6); (3) feces from TS at 4 time points (nonfeeding, 30 and 60 feeding days, and stop feeding 30 days) with probiotics supplementation (n = 7). The results indicated SHS had the highest Firmicutes abundance, the thinnest back-fat, and the lowest expression of C/EBPβ, C/EBPδ, ATGL, CFD, and SREBP1. Some bacteria orders and families could be potential biomarkers for sheep breeds with a distinct distribution of bacterial abundance, implying the host genotype is predominant in shaping unique microbiota under a shared environment. The microbiota diversity and Bifidobacterial populations significantly changed after 60 days of feeding but restored to its initial state, with mostly colonies, after 30 days ceased. The microbiota composition was greatly different between the small and large intestines, but somewhat different between the large intestine and feces; feces may be reliable for studying large intestinal microbiota in ruminants.